Alpine Newts (Ichthyosaura alpestris) Avoid Habitats Previously Used by Parasite-Exposed Conspecifics - Daversa, David R.; Manica, Andrea; Bintanel Cenis, Héctor; Lopez, Pilar; Garner, Trenton W. J.; Bosch, Jaime (Frontiers in Ecology and Evolution, 2021)
Many organisms avoid habitats posing risks of parasitism. Parasites are not generally conspicuous however, which raises the question of what cues individuals use to detect parasitism risk. Here, we provide evidence in alpine newts (Ichthyosaura alpestris) that non-visual cues from parasite-exposed conspecifics inform habitat avoidance. Alpine newts breed in aquatic habitats and occasionally move among adjacent terrestrial habitat during breeding seasons. We completed experiments with newts whereby individuals had access to both habitats, and the aquatic habitats varied in prior occupancy by conspecifics with different histories of exposure to the parasitic skin fungus, Batrachochytrium dendrobatidis (Bd). Continuous filming of newt activity for 2 days provided little evidence that prior use of aquatic habitats by conspecifics, regardless of their Bd exposure history, immediately influenced newt habitat use. However, newts that encountered aquatic habitats used specifically by Bd-exposed conspecifics on day 1 spent less time aquatic on day 2, whereas other newts did not alter habitat use. Responses could have been elicited by cues generated by Bd stages on the conspecifics or, perhaps more likely, cues emitted by the conspecifics themselves. In either case, these observations suggest that newts use non-visual cues sourced from exposed conspecifics to detect Bd risk and that those cues cause newts to avoid aquatic habitats. Bd may therefore influence host behaviour in early phases of interactions, and possibly before any contact with infectious stages is made, creating potential for non-consumptive effects.